Ineffective implementation of risk management among sub-contractors: a conceptual paper / Nurqameela Md Radzi, Kartina Alauddin and Mohmad Mohd Derus - Md Radzi, Nurqameela; Alauddin, Kartina; Mohd Derus, Mohmad (2018)
Construction is a high-risk activity, which must be managed from procurement, throughout the design process and to the end of the construction stage. It involves professionals of different set of skills and expertise. Each party in the construction industry plays an important role in order to complete any project within the timeline, the lowest cost and the best quality product. The main cause problems occur in construction industry is due to ineffective implementation of risk management. The methods used in this research are mixed methods which were qualitative and quantitative. This research advocates the strategies that can overcome ineffective implementation of risk management among sub-contractors. Besides, this research also will provide a better understanding on the effective implementation of risk management practice in Malaysia and how the strategies can be implemented or used as guidelines by construction companies especially sub-contractors in their respective projects.